Statistical convergence of nets on locally solid Riesz spaces - Temizsu, F.; Aydın, Abdullah (Springer Science and Business Media B.V., 2022)
The statistical convergence is handled for sequences with the natural density, in general. In a recent paper, the statistical convergence for nets has been studied and investigated by developing topology-free techniques in Riesz spaces. In this paper, we introduce the statistically topological convergence for nets on locally solid Riesz spaces with solid topologies. Moreover, we give the notion of statistical continuity on locally solid Riesz spaces. © 2021, The Author(s), under exclusive licence to The Forum D’Analystes.
Keywords: Finitely additive measure; Riesz spaces; Solid topology; Statistical continuous operator; Statistical convergence of nets